2010
DOI: 10.1113/jphysiol.2010.195941
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic neural activation: an ordered affair

Abstract: Is there an ordered pattern in the recruitment of postganglionic sympathetic neurones? Using new multi-unit action potential detection and analysis techniques we sought to determine whether the activation of sympathetic vasomotor neurones during stress is governed by the size principle of recruitment. Multi-unit postganglionic sympathetic activity (fibular nerve) was collected from five male subjects at rest and during periods of elevated sympathetic stress (end-inspiratory apnoeas; 178 ± 37 s(mean ± S.D.)). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
109
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 32 publications
12
109
0
Order By: Relevance
“…Also, the presence of faster conduction velocity axons with chemoreflex activation is consistent with earlier observations that conduction velocity of spinal descending pathways during chemoreflex stimulation (5.5 ± 0.9 m/s) were faster than for baroreflex activation (3.3 ± 0.7 m/s) (144). In view of these findings, the larger action potential in the faster conducting axons observed by Steinback et al (266) may form part of a specific pathway for chemoreflex neurovascular control. The neurovascular impact of these latent but recruitable subpopulations of sympathetic axons remains difficult to assess because the chemoreflex stress under which they were induced likely modifies the vascular response.…”
Section: Characteristics Of Postganglionic Sympathetic Dischargesupporting
confidence: 86%
See 2 more Smart Citations
“…Also, the presence of faster conduction velocity axons with chemoreflex activation is consistent with earlier observations that conduction velocity of spinal descending pathways during chemoreflex stimulation (5.5 ± 0.9 m/s) were faster than for baroreflex activation (3.3 ± 0.7 m/s) (144). In view of these findings, the larger action potential in the faster conducting axons observed by Steinback et al (266) may form part of a specific pathway for chemoreflex neurovascular control. The neurovascular impact of these latent but recruitable subpopulations of sympathetic axons remains difficult to assess because the chemoreflex stress under which they were induced likely modifies the vascular response.…”
Section: Characteristics Of Postganglionic Sympathetic Dischargesupporting
confidence: 86%
“…With this approach Steinback et al (266) reported higher firing rates of axons already active at baseline, as well as the recruitment of latent, higher threshold, and faster conducting sympathetic axons, during chemoreflex activation induced via prolonged breath holds (Fig. 6).…”
Section: Characteristics Of Postganglionic Sympathetic Dischargementioning
confidence: 94%
See 1 more Smart Citation
“…Evidence from this approach indicates that APs vary in size Steinback et al 2010) with larger APs demonstrating a faster conduction velocity . Thus these larger voltage signals appear to be from larger axons supporting evidence for the varied size of postganglionic C fibers (Fazan et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, we have observed that APs within the MSNA neurogram vary in size and conduction velocity Steinback et al 2010). Importantly, there is a range of AP sizes that are variously expressed over time.…”
mentioning
confidence: 98%